(untitled) (CIPEEX, 2025)
The project aims to reduce the manual workload in enrollments, report generation, and attendance tracking by developing software that enhances academic data management. This system will improve internal communication and make information exchanges between students, parents, and teachers more efficient. The implementation of a centralized academic platform will integrate key administrative and pedagogical functions, including student records, attendance, and enrollment. User feedback will be continuously gathered from teachers, students, and parents to optimize the system according to their needs. This approach will provide better control over institutional performance, facilitating quick interventions through detailed reports and real-time attendance data, ultimately increasing the institution’s efficiency and profitability. The automated system will optimize administrative processes, offer detailed student performance monitoring, and directly support learning. The results will demonstrate enhanced administrative efficiency and a positive impact on the quality of education provided.